Studi Literatur Pada Model Pembelajaran ICARE Terhadap Keterampilam Berpikir Kreatif Peserta Didik Pada Materi Momentum&Impuls - Ranadhana, Ari (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2020)
One effort to improve the quality of the learning process by applying a learning model. Critical thinking can be interpreted as an effort to examine the truth of an information using the availability of evidence, logic, and awareness of bias. Lack of concept knowledge in students on the momentum material that is associated with daily life. There has been an increase in students by applying the ICARE learning model. Creative thinking is expected that students will be able to relate everyday life to the impulse momentum material with the problem to be solved